CAD/CAE Integrated Design of High-speed Train Gear Couplings - Mao Dongjin; Shang Yuejin; Xue Hai; Zeng Si'ao; Ma Sainan (Jixie chuandong)
In order to improve the design efficiency of high-speed train gear coupling and optimize the design structure, the CAD/CAE technology is used to carry out the integrated design. The CAD software is used to design and virtually assemble the drive device and a motion simulation analysis of the drive device is conducted, which produce the wheel set linear speed of the traction motor under the rated speed and the maximum speed. The CAE software is used to adjust the drum gear. The coupling is subjected to static strength analysis and safety check to ensure its safety in service; the results show that the linear wheel speed of the traction motor is 243.3 km/h at the rated speed and 349.1 km/h at the maximum speed, respectively, which satisfy high-speed operating conditions. The maximum stress of the drum-shaped gear coupling under balanced conditions and maximum angular displacement conditions are 391 MPa and 403 MPa respectively, which meet the requirements of safe operation. The above-mentioned coupling CAD/CAE integrated design method provides a reference for its optimization.